2021
DOI: 10.1270/jsbbs.20163
|View full text |Cite
|
Sign up to set email alerts
|

Genetic region responsible for the differences of starch properties in two glutinous rice cultivars in Hokkaido, Japan

Abstract: Starch properties are major determinants of grain quality and food characteristics in rice (Oryza sativa L.). Control of starch properties will lead to the development of rice cultivars with desirable characteristics. We performed quantitative trait locus analysis and detected a putative region on chromosome 2 associated with phenotypic variation of starch properties in two glutinous rice varieties developed in the Hokkaido region of Japan: 'Kitayukimochi', which has a low pasting temperature and creates soft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Once genes associated with desirable traits are introduced, they can spread to the entire population (Fujino et al 2019b). Previously, we demonstrated that major genes associated with desirable traits in elite varieties were introduced into the local gene pool, such as rice blast disease resistance Pi-cd, plant type Hd1, and eating quality SbeIIb (Fujino et al 2019b, d;Ikegaya and Ashida 2021). Understanding genetic diversity involved in local varieties may be of use in crop breeding programs for rice and other crops.…”
Section: Discussionmentioning
confidence: 99%
“…Once genes associated with desirable traits are introduced, they can spread to the entire population (Fujino et al 2019b). Previously, we demonstrated that major genes associated with desirable traits in elite varieties were introduced into the local gene pool, such as rice blast disease resistance Pi-cd, plant type Hd1, and eating quality SbeIIb (Fujino et al 2019b, d;Ikegaya and Ashida 2021). Understanding genetic diversity involved in local varieties may be of use in crop breeding programs for rice and other crops.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the loss of BEIIb in wx ae , derived from EM16 (selected from the MNU-mutagenized population of Kinmaze), decreased the number of short amylopectin chains (DP < 15) and increased the number of long amylopectin chains (DP > 15), which in turn increased the gelatinization temperature (to 83 °C) as well as the pasting temperature [ 48 ]. Similarly, Shirokumamochi, possessing BEIIb derived from Kitaake, contains Leu94Val and His196Arg substitutions and produced harder rice cakes compared to Kitayukimochi [ 49 ], likely because of a slight reduction in BEIIb activity. Although the genetic factors affecting amylopectin branch structures in the vast majority of other glutinous rice cultivars remain unknown, the results of the present study support the idea that rice lines containing starch with fewer short amylopectin chains and more long amylopectin chains exhibit higher gelatinization and pasting temperatures and produce harder rice cakes, whereas those with starch containing more short amylopectin chains and fewer long amylopectin chains exhibit lower gelatinization and pasting temperatures and produce softer rice cakes [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cultivation management followed the standard procedures used at the Hokkaido Agricultural Research Center as described by Ikegaya and Ashida (2021). Sowing and transplanting were performed on 20 April and 20 May 2020, respectively.…”
Section: Growth Conditionsmentioning
confidence: 99%
“…Mutant BEI, BEIIa, and BEIIb lines have been isolated from rice (Nakamura 2002, Nishi et al 2001, Satoh et al 2003a, 2003b. Previously, starch branching enzyme IIb (SbeIIb) was identified on chromosome 2 as a candidate gene for the differences in starch properties between glutinous rice varieties in Hokkaido (Ikegaya and Ashida 2021). SbeIIb is known as an amylose extender (AE) gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation